Specialized versus versatile intergenerational transmission of violence: a new approach to studying intergenerational transmission from violent versus non-violent fahters; latent class analysis - Besemer, Sytske (Journal of quantitative criminology, 2012)
This paper investigates whether fathers who have been convicted of a violent offense transmit criminal and violent behavior more strongly than fathers who were convicted, but never for violence. First, a more traditional approach was taken where offending fathers were divided into two groups based on whether they had a violence conviction. Secondly, Latent Class Analysis (LCA) was performed to identify two classes of fathers, one of which was characterized as violent. Sons of fathers in this class had a higher risk of violent convictions compared with sons whose fathers were in the other class.